Dampak Krisis Keuangan Global Terhadap Pertumbuhan Ekonomi di Indonesia - Lala Puspita Sari; Muslihah Muslihah; Rifki Mutohari; Rasidah Novita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article examines how Indonesia's economic growth was affected by the global financial crisis brought on by the US subprime mortgage crisis. In addition to having an effect on Indonesia through trade and financial channels, this crisis led to a downturn in the demand for consumer spending, investment, and exports in developing nations. This decrease was a contributing factor to the drop in Indonesia's GDP. The research approach adopted is literature study with analysis of pertinent literature. In addition, this article also covers comments on the causes of the crisis from conventional and Islamic economic viewpoints, as well as the significance of market reform to prevent excessive speculation. The author highlights how using the concepts of Islamic finance can be beneficial enhance the domestic financial sector to increase its resilience to external shocks and avert future crises.